Molecular weight characterization of cellulose using ionic liquids - Yan Zhou (Elsevier, 2021)
Cellulose, the most abundant natural polymer on the planet, is the major polysaccharide produced by plant photosynthesis. It has many advantages, such as renewability, tremendous reversibility, complete biodegradability, excellent biocompatibility, high mechanical property and structural designability. The molecular weight and polydispersity index are the key parameters of cellulose materials. Measurement of the molecular weight characteristics of cellulose is of great significance for effectively utilizing cellulose resources and comprehensively understanding the relationship between structure and property. In this review, we summarize the methods used to characterize the molecular weight of cellulose and focus on the detailed applications of ionic liquids for such characterization.